Penerapan Buerger Allen Exercise Pada Nilai Ankle Brachial Index Pasien Diabetes Melitus Tipe 2 di Kelurahan Sewu - Anggita Sekar Maharani; Tri Susilowati (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Diabetes mellitus is a chronic disease that can cause complications in the form of peripheral vascular disease. According to data from the World Health Organization (WHO) in 2022, around 422 million people in the world suffer from DM. The prevalence of DM sufferers in 2023 will reach 3,579 cases. Type 1 DM cases reached 2,541 cases, Type 2 DM cases reached 1,038 cases. One non-pharmacological therapy is the Buerger Allen Exercise (BAE). Objective: To describe the results of the comparison of Ankle Brachial Index (ABI) values ​​before and after implementing BAE in Type II Diabetes Mellitus. Method: This research design uses a case study method, a descriptive research method and observing events that have occurred by observing the ABI values ​​for 2 respondents. 1 time in 6 consecutive days for 15 minutes. The instruments used in this research were a 45° angle meter made of plywood, chairs, blankets, stopwatch, sphygmomanometer, SOP sheet, observation sheet to record developments. Conclusion: The application of BAE could potentially increase the ABI value in Diabetes Mellitus in both respondents.